Pregnant in prison: An integrative literature review. Issue 1 (February 2020) - Baldwin, Adele; Sobolewska, Agnieszka; Capper, Tanya
Abstract: Background: Pregnant women in prisons are recognised as a marginalised group. However, there is a limited understanding of the women's unique maternity needs and how correctional institutions and maternity service providers respond to these needs. Aim: The aims of the review are threefold. 1. Identify pregnant women's needs during the antenatal, birthing and postnatal periods in prison. 2. Examine how the pregnant incarcerated women's needs are met by the correctional institutions. 3. Explore what maternity services are available and how these services are provided. Method: An integrative literature review was undertaken. A comprehensive search strategy using seven electronic databases resulted in the retrieval of 363 articles. Of them, 32 peer-reviewed studies met the final selection criteria and were included in this review which utilised the Critical Appraisal Skills Program tools and adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flowchart. Thematic analysis identified universal themes. Findings: Three dominant themes emerged related to the experience of pregnant women in prison: (1) risks and vulnerability factors; (2) prison enablers and supports; and (3) prison barriers. Extant research on risks and vulnerability factors is disproportionate to research examining how prisons can enable or obstruct responding to the women's perinatal needs. Limited research on the midwifery support available to the women in prison is available. Significantly, only two out of 32 reviewed papers include research directly conducted with the pregnant women in prison. Conclusion: Pregnant women in prisons have complex needs. More research is required to understand how prisons can enhance the pregnancy experience by engaging pregnant women in prisons as research participants.